Removal of hydrogen sulphide (H2S) by empty fruit bunch hydrogel biochar composite (EFB-HBC) / Nor Hidayah Meri - Meri, Nor Hidayah (2019)
This research successfully proved that HBC also has potential in adsorption of Hydrogen Sulphide (H2S) from gas effluent. The HBC from this study were derived from Empty Fruit Bunch (EFB) biochar which were produced by using microwave pyrolysis under 1000 W for 30 minutes with 150 mL/min of nitrogen flow. Followed by the EFB biochar were treated with two different chemical agent (HCl) and (H2O2) and labelled as EFB Biochar H100 and EFB Biochar P100 respectively.